Familial and Socio-Environmental Predictors of Obesity Among School Children in Selangor and Kuala Lumpur - Tung, Serene En Hui (2011)
A cross-sectional study was carried out to determine the familial and socio-environmental predictors of obesity among 1430 primary school children aged 9-12 years-old (mean age = 10.3 ± 0.8 years) in Selangor and Kuala Lumpur (Klang Valley). Body mass index (BMI) was used as a measure of obesity. Subjects were invited to complete a self-administered questionnaire, including Child Feeding Questionnaire (CFQ) and Determinants of Adolescent Social Well-being and Health (DASH). Besides, body mass index (BMI) was used as a measure of obesity. The respondents comprised of 41.5% of males and 58.4% female children encompassed 56.3% Malay, 25.6% Chinese, 16.6% Indian and 1.4% Others. A total of 17.9% (293) were overweight while 16.0% (263) were obese. More females (10%) than males (7.9%) were found to be overweight. However more males (9.0%) than females (7.0%) were obese. Familial factors were measured and most parents perceived their weight (53.1%) and their child’s weight (57.1%) to be balanced. Parents were also responsible for feeding their child (10.1 ± 2.1), concern of child’s weight status (7.5 ± 2.6), highly restrict child’s eating (11.4 ± 2.3), moderately pressure child to eat (6.4 ± 1.8), highly encourage healthy eating and physical activity (9.2 ± 1.1), and moderately makes sugar dense foods and vegetables available at home (15.9 ± 2.8; 9.2 ± 1.5). Parent’s and children dietary intake was found to be similar respectively: fruits and vegetables (19.5 ± 3.1; 18.2 ± 3.6), meat (8.6 ± 1.4; 8.5 ± 1.6), fast food (5.8 ± 0.9; 5.5 ± 1.0), snack (8.3 ± 1.7; 7.7 ± 1.8) and sweet drinks (5.7 ± 1.2; 5.6 ± 1.2) consumption. Children’s physical activity (16.5 ± 3.7) was reported to be higher than parent’s physical activity involvement (13.0 ± 3). Socio-environment factors were also measured where parent’s moderately perceived their neighbourhood to be safe (14.8 ± 3.1) and most neighbourhood were reported to only have fields as recreational facilities (1.6 ± 1.0). A significant association between child’s weight status and parents weight status was found (χ2= 204, p=0.015). The relationship was positive between children’s BMI and parent’s BMI (r=0.129, p ≤ 0.01). Other familial factor positively correlated with children’s BMI were concern about child’s weight (r=0.125, p ≤ 0.01) and restriction (r= 0.057, p ≤ 0.05). However, pressure to eat (r= -0.135, p ≤ 0.01) on children was negatively associated with children’s BMI. Socio-environmental factors were measured to look at the relationship with children’s BMI. Neighbourhood safety perception (r= -0.053, p ≤ 0.05) was negatively correlated with children’s BMI. Logistic regression reported the risk of overweight and obese in children was found among female children (OR=0.538; 95% CI = 0.421, 0.687), parents of increasing BMI (OR=1.055; 95%=1.028, 1.082), parent’s of increasing concern about child’s weight (OR=1.082; 95%= 1.030; 1.127), increasing practice of restriction (OR=1.059; 95%= 0.999; 1.123), increasing pressure to eat (OR=0.857; 95% = 0.801-0.916) and decreasing neighbourhood safety perception of parents (OR=0.951; 95% =0.913; 0.990). Information from this study recommends that parents should be informed of the importance of familial and socio-environmental influence on child’s weight status and intervention programs should mainly focus on educating parents on these areas of influence on the child.